Current tuned slotted Y‐branch laser for wafer thickness measurements with THz radiation. Issue 24 (12th September 2021) - Surkamp, N.; Gerling, A.; O'Gorman, J.; Honsberg, M.; Schmidtmann, S.; Nandi, U.; Preu, S.; Sacher, J.; Brenner, C.; Hofmann, M. R.
Abstract: A slotted Y‐branch laser diode that emits two spectral modes at a difference frequency of about 1 THz is investigated in the context of photonic based cw‐THz measurements. The beating frequency of the emitted laser light can be tuned by ±10.5 GHz around 1 THz by changing the applied laser current, which allows for potentially fast measurements. A second spectral window of ±6.5 GHz was found at 850 GHz. Pointwise scanning of the difference frequency is demonstrated with thickness determination of HRFZ‐Si wafer samples as a possible application scenario.